Hubungan beban kerja dengan stress kerja pada pekerja lapangan - Andi Rahmadi; Rahma Elliya; Prima Dian Furqoni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2022)
Physical workload and chronic psychosocial stress among sugar cane plantation workers Background : The effect of work stress on workers has an influence on the professionalism of workers. Based on the results of the pre-survey research dated 1-15 August 2019 from 20 workers at PT. Indolampung Perkasa Gedung Meneng District, Tulang Bawang Regency, it is known that as many as 18 (90%) expressed insomnia, anxiety, irritability, out of 20 (100%) respondents revealed that they often worked beyond the hours specified at the start of planting or during harvest and things it is not adjusted for the compensation received. Objectives: The relationship between workload and work stress on field workers at PT. Indolampung Perkasa Gedung Meneng District Tulang Bawang Regency in 2019. Research Methods: Type of quantitative research, cross sectional design. The population of this study was 250 respondents with a sample of 154, when the study was conducted in July 2019. Primary data collection, directly to respondents. Univariate data analysis using frequency distribution and bivariate using chi square analysis. Results: It is known that 97 (63.0%) respondents did not experience work stress, 98 (66.2%) respondents had light workloads. There is a relationship between workload and work stress events in field workers in Division III and IV of PT. Indolampung Perkasa Gedung Meneng District Tulang Bawang Regency in 2019 (p-value = 0.001 OR 3,434). Conclusion: There is a relationship between workload and work stress events in field workers in Division III and IV of PT. Indolampung Perkasa Gedung Meneng District Tulang Bawang Regency in 2019. Suggestions Provide activities / events such as religious spiritual splash, training seminars on emotional and spiritual intelligence and Provide activities such as recreation for employees and families. Keywords: Work Stress, Workload, Field Workers Latar Belakang: Pengaruh stress kerja pada pekerja memiliki pengaruh terhadap profesionalitas pekerja. Berdasarkan hasil pra survey penelitian tanggal 1-15 Agustus 2019 dari 20 pekerja di PT. Indolampung Perkasa Kecamatan Gedung Meneng Kabupaten Tulang Bawang, diketahui bahwa sebanyak 18 (90%) mengungkapkan susah tidur, gelisah, mudah marah, dari 20 (100%) responden mengungkapkan bahwa sering bekerja melebihi jam yang di tentukan saat dimulai penanaman maupun saat panen dan hal tersebut tidak disesuaikan dengan imbalan yang diterima. Tujuan: Diketahui hubungan beban kerja dengan stress kerja pada pekerja lapangan di PT. Indolampung Perkasa Kecamatan Gedung Meneng Kabupaten Tulang Bawang tahun 2019. Metode: Jenis penelitian kuantitatif, rancangan cross sectional. Populasi dari penelitian ini adalah 250 responden dengan sampel 154, waktu penelitian telah dilaksanakan pada bulan Juli 2019. Pengumpulan data secara primer, langsung kepada responden. Analisis data secara univariat menggunakan distribusi frekuensi dan bivariat menggunakan analisi chi square. Hasil: Diketahui bahwa sebanyak 97 (63,0%) responden tidak mengalami stres kerja, sebanyak 98 (66,2%) responden memiliki beban kerja ringan. Ada hubungan antara beban kerja dengan kejadian stres kerja pada pekerja lapangan di Divisi III dan IV PT. Indolampung Perkasa Kecamatan Gedung Meneng Kabupaten Tulang Bawang tahun 2019 ( p-value = 0,001 OR 3,434) Simpulan: Ada hubungan antara beban kerja dengan kejadian stres kerja pada pekerja lapangan di Divisi III dan IV PT. Indolampung Perkasa Kecamatan Gedung Meneng Kabupaten Tulang Bawang tahun 2019. saran Memberikan kegiatan / acara seperti siraman rohani keagamaan, seminar pelatihan tentang kecerdasan emosi dan spiritual dan Memberikan kegiatan seperti rekreasi bagi karyawan dan keluarga